2012
DOI: 10.1021/ac3023586
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Detection of Dopamine Using a Carbon Nanotube Network Microfluidic Flow Electrode

Abstract: The electrochemical measurement of dopamine (DA), in phosphate buffer solution (pH 7.4), with a limit of detection (LOD) of ∼5 pM in 50 μL (∼ 250 attomol) is achieved using a band electrode comprised of a sparse network of pristine single-walled carbon nanotubes (SWNTs), which covers <1% of the insulating substrate. The SWNT electrodes are deployed as amperometric (anodic) detectors in microfluidic cells, produced by microstereolithography, designed specifically for flow injection analysis (FIA). The flow cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 41 publications
2
66
0
Order By: Relevance
“…This is as expected for this design of flow cell. 28,39 Even though the residence time of electroanalyte in contact with the detector electrode is greatly reduced in FIA and under flow potential fouling products can be washed away downstream, 28 for HS − oxidation, repeat injections at a fixed concentration (25 μM) and V f = 1 cm 3 min −1 showed a decrease in peak current (data not shown), suggesting electrode passivation, most likely with electrodeposited sulfur (vide infra). The mobile phase contained 0.1 M KNO 3 , adjusted to pH 10 through the use of potassium hydroxide.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…This is as expected for this design of flow cell. 28,39 Even though the residence time of electroanalyte in contact with the detector electrode is greatly reduced in FIA and under flow potential fouling products can be washed away downstream, 28 for HS − oxidation, repeat injections at a fixed concentration (25 μM) and V f = 1 cm 3 min −1 showed a decrease in peak current (data not shown), suggesting electrode passivation, most likely with electrodeposited sulfur (vide infra). The mobile phase contained 0.1 M KNO 3 , adjusted to pH 10 through the use of potassium hydroxide.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…88 In an attempt to replace expensive platinum catalysts for the oxygen reduction reaction in fuel cells, carbon nanotube supports have been investigated as potential catalysts in this extremely useful process. 111 A novel demonstration of electrochemical carbon nanoreactors was reported by McSweeney et al by the encapsulation of methylcyclopentadienyl manganese tricarbonyl, Cp Me Mn(CO) 3 , within narrow SWCNT. However, in this case, the encapsulation of iron nanoparticles 86 and phosphorus 87 dopants alters the electronic properties and the catalytic activity of the carbon nanotube external surface, demonstrating the influence that confined species can have on the host carbon nanotube and highlighting the symbiotic nature of such host-guest interactions.…”
Section: View Article Onlinementioning
confidence: 99%
“…They showed that the ultra-high porosity arrays resulting from this CVD technique gave enhanced particle interception and subsequently allowed microfluidic cell separation (equivalent to cell sorting). In order to fabricate SWCNT electrodes that could be used to detect dopamine in a flow stream, Sansuk et al (2012) successfully formed a two-dimensional sparse network of SWCNTs on an insulating Si/ SiO 2 substrate via a catalyzed CVD technique. It was shown that this detector effectively improved dopamine detection.…”
Section: Carbon Nanotubes: Synthesis and Integration Techniques Into mentioning
confidence: 99%